Light-induced switching of polymer-surfactant interactions enables controlled polymer thermoresponsive behaviour. Issue 47 (18th May 2021) - Weißenborn, Eric; Droste, Jörn; Hardt, Michael; Schlattmann, Daniel; Tennagen, Celine; Honnigfort, Christian; Schönhoff, Monika; Hansen, Michael Ryan; Braunschweig, Björn
Abstract : Hydroxypropyl cellulose and arylazopyrazole mixtures for remote control of particle size and solution viscosity using light and temperature stimuli. Abstract : Hydroxypropyl cellulose (HPC) and arylazopyrazole (AAP) mixtures can be remotely controlled by light and temperature. We show that the hydrophobic interactions between HPC polymers with AAP surfactants can be drastically changed by changing the surfactants configuration through E / Z photo-isomerization. E -AAP interacts strongly with HPC which causes a dramatic increase of the critical temperature T c of the polymers' phase transition and a loss of the coil-to-globule transition, while the hydrophobic interactions of HPC with Z -AAP are drastically reduced. As a result, E / Z photo-isomerization of AAP in mixtures with HPC offers remote control of the polymers phase transition, size and solution viscosity in an unprecedented way, and allows for new directions in colloid science.